PENGUKURAN DOSIS EFEKTIF ORGAN TYROID DAN MATA PADA PEMERIKSAAN MAMMOGRAFI - Firmansyah, Lody (IAIN Batusangkar, 2016)
A research has been done about the effective dose measurement of thyroid and eye organ on mammography examination. The aims of the research is to determine the radiation dose absorbed by the thyroid organ and eye examination Mammography. This research uses TLD-100 as a radiation measuring instrument. The data retrieval process has taken place in Parahita Laboratorium, Jakarta by collecting five of patients data to have Mammography radiology examination, the research is done by putting the TLD-100 in every side of thyroid organ and eye to know the value radiation dose which occurs in Mammography examination. Eksposi factors used in this study was 29 kV and 250 mA. The result of this research is obtained the value of the dose absorbed by the thyroid organ and less than the limit value of existing dose of 0,7 mSv, To analysts equivalent dose in patients who received organ Mammography is quite safe because less than the value standard dose limits specified.Key words : mammography, radiation dose, TLD